ANALYSIS AND MANUFACTURE OF PIPE ROLL BENDING MACHINE - ARIES ABBAS; DENNY PRUMANTO; HANDIKA BUDIARTO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Pipe rolling machine is a machine for rolling pipes or bending pipes. The purpose of the analysis and manufacture of the machine is to make pipe bending work easier because the machine bends automatically according to the desired degree. The design process for this pipe rolling machine includes: making design concepts, identification of materials, identification of machines and equipment used, and identification of drawings. The thing that needs to be considered in the manufacture of this pipe rolling machine is the density of the connections on the upper frame and lower frame legs so that vibration occurs when the machine is operating. This machine has dimensions of length 500 mm, width 320 mm, 500 mmn machine performance testing is carried out by testing directly to make pipe rolls. The results of testing the time needed to make one roll pipe is 20 minutes, with a rotation speed of 1400 Rpm.